Estudo das propriedades estruturais e óticas de compostos aluminoboratos e aluminogermanatos puros e dopados com íons terras-raras - Faria Filho, Fausto de Melo (2017)
The objective of this thesis is study aluminogermanate and aluminoborate compounds containing lanthanide ions for photonic applications, especially light emitting diodes, as phosphors. Samples were prepared by sol-gel and polymeric precursor method (Pechini method). It was studied pure and doped Al6Ge2O13 with 1 mol% Eu3+ or Er3+ , heat treated at 1000 °C; 1 mol% Eu3+ doped xAl2O3+(1-x)B2O3, for x values: 0.33; 0.50; 0.60; 0.66; 0.75 and 0.80 under heat treatments at 800, 900 or 1000 °C; and the Al4B2O9 phase with xNd3+/ yYb3+, where x, y = 1, 0; 1, 1; 1, 2; 1, 4; 1, 8; 0, 1; 2, 1; 4, 1 and 8, 1, heat treated at 900 °C. The powders samples were characterized by X-ray diffraction, infrared vibrational spectroscopy, thermal analysis, and transmission electron microscopy. Diffuse reflectance spectra and photoluminescence emissions were collected under excitation at 394 nm for Eu3+ doped samples, at 378 and 977 nm for Er3+ doped samples, at 804 nm for Nd3+/Yb3+ doped samples and at 365 nm for pure samples. The Er3+ or Eu3+ doped aluminogermanate sample presented the Al6Ge2O13 crystalline phase identified by JCPDS card number 71-1061 after annealings at high temperatures. Absorption spectra in the infrared region showed Al-O-Ge and Al-O type bonds. The Eu3+ doped Al6Ge2O13 samples when excited at 394 nm showed red emission and the spectra analysis lead us to conclude that the lanthanides were located in a homogeneous environment with low symmetry. The Er3+ doped Al6Ge2O13 sample showed emission band in the infrared region with full width at half maximum of around 48 nm when excited at 977 nm. The band gap values were determined being between 4.19 and 4.30 eV. The Eu3+ doped xAl2O3+(1-x)B2O3 compositions presented the crystalline phase Al4B2O9 identified by JCPDS card number 29-0010. AlO6, AlO4, BO4 and BO3 groups were identified by FTIR technique. For these compositions, the emission spectra in the visible region showed a homogeneous environment with low symmetry. The Eu3+ doped 0.66Al2O3+0.34B2O3 sample possess the highest photoluminescence emission, after heat treatments at 900 °C . The lifetime of the Eu3+ 5D0 excited level were between 1.4 and 2.1 ms, depending on the B2O3 concentration and annealing temperature. The optical band gap was also determined having values between 3.72 and 4.42 eV. The Nd3+/Yb3+ doped Al4B2O9 samples present an efficient energy transfer between lanthanide ions and the best relative concentration was 1Nd3+ / 2Yb3+. The decay time of the emission at 1080 nm (975 nm) as function the Nd3+ concentration shows a maximum value around 120 μs at concentration of 4 mol% (around 200 μs for 2 mol%). On the other hand, changing the Yb3+concentration, the maximum decay time for emission at 1080 nm (975 nm) was around 100 μs (175 μs) for 1 mol% of Yb3+. In short, the materials studied are excellent candidates for application as luminophores in various technologies, such as LED´s and displays.